Lance Fortnow, The Golden Ticket: P, NP, and the Search for the Impossible, Princeton University Press, 2013, ISBN 978-0-691-15649-1. - TRÎMBIȚAS, Radu (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
The class P is the class of problems which can be solved in polynomial time on deterministic machines. In Complexity Theory tractable is synonym to having solution algorithm with polynomial runtime. The class NP is the class of problems which can be solved in polynomial time on nondeterministic machines, or equivalently having solutions which can be checked in polynomial time.